MODELING THE PROCESSES OF KNOWLEDGE SHARING MANAGEMENT BETWEEN PROJECT GROUPS - Dmitry V. Zalesov (Статистика и экономика)
The article is devoted to conception of modeling the processes of knowledge sharing management between project groups for improving efficiency of communications management in project activities. The author identifies a number of key issues related to the knowledge circulation between projects, signifies the importance of the study subject and offers a model for evaluating the applicability of knowledge in projects and a method of knowledge refinement in project activities.